Efficacy of selected environmentally friendly management options against the fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) and their cost-effectiveness on maize Zea mays in Burundi - Alexis Mpawenimana; Ruth Kahuthia-Gathu; Maina Mwangi; Mawufe Komi Agbodzavu; Albert Fomumbod Abang; Yendouban Lamboni; Celestin Hitimana; Déo Kantungeko; Patrick Mutuo Kiiti; Komi Kouma Mokpokpo Fiaboe (International Journal of Tropical Insect Science, 2026)

Adoption and dis-adoption of push-pull technology in East Africa: Evidence from survival analysis and machine learning - Denis Waiswa; Beatrice Wambui Muriithi; Alice Warukira Murage; Dave Mwangi Ireri; Fredah Maina; Fahri Yavuz (Crop Protection, 2026)

Enhancement of surimi gels using phosphorylated cellulose nanofibers - Berkani Somia; Lei Zhang; Ning Ren; Xue Gao; Cancan Shan; Mei Cui; Rongxin Su; Maina Mwangi; Renliang Huang (Food Structure, 2026)

Integrated management of root-knot nematodes on tree tomato - Stanlous Juma Waswa; Waceke J. Wanjohi; Maina Mwangi (Rhizosphere, 2025)

Improving the performance properties of plastic-sand bricks with Kaolin Clay - Kimendren Gounden; Festus Maina Mwangi; Turup Pandurangan Mohan; Krishnan Kanny (Environment, Development and Sustainability, 2024)
This study analyses the performance properties of plastic-sand bricks through experimental work on the use of High-Density Polyethylene (HDPE) and river sand in the first stage using six different sand: plastic ratios (60s:40p; 65s:35p; 70s:30p; 75s:25p; 80s:20p; 85s:15p) and in the second stage the effects of adding 1%, 5%, and 10% of Kaolin Clay. Five different tests were conducted to assess the bricks’ resistance to environmental factors. The key findings indicate that the lowest water absorption rate of 0.39% was achieved with a 60s:40p ratio, attributed to the addition of 10% Kaolin Clay. Scanning Electron Microscopy (SEM) analysis revealed that Kaolin Clay effectively fills voids between particles, enhancing the structural integrity and reducing water absorption of the brick samples. Electrical resistance readings indicated that all plastic-sand brick samples had a resistance of 0.01 ohms, classifying the composite material as an insulator. Contact angle tests demonstrated that all brick samples resisted immediate water absorption, and no alkali deposits were detected. The lowest linear burning rate was observed in the 75s:25p ratio with a 10% addition of Kaolin Clay. Overall, the findings suggest that HDPE plastic waste can be repurposed to produce eco-friendly plastic-sand bricks, significantly mitigating environmental plastic waste. These composite materials show promise for use as bricks, pavers, and other non-load-bearing applications in the construction industry, providing a sustainable alternative to traditional building materials. This research highlights the potential for HDPE based plastic-sand bricks to contribute to a more sustainable construction sector.

Prioritization of invasive alien species with the potential to threaten agriculture and biodiversity in Kenya through horizon scanning - Joseph Mulema; Roger Day; Winnie Nunda; Komivi Senyo Akutse; Anani Y. Bruce; Sospeter Gachamba; Solveig Haukeland; Ruth Kahuthia-Gathu; Staline Kibet; Asenath Koech; Thomas Kosiom; Douglas Watuku Miano; et al. (Biological Invasions, 2022)
Invasive alien species (IAS) rank among the most significant drivers of species extinction and ecosystem degradation resulting in significant impacts on socio-economic development. The recent exponential spread of IAS in most of Africa is attributed to poor border biosecurity due to porous borders that have failed to prevent initial introductions. In addition, countries lack adequate information about potential invasions and have limited capacity to reduce the risk of invasions. Horizon scanning is an approach that prioritises the risks of potential IAS through rapid assessments. A group of 28 subject matter experts used an adapted methodology to assess 1700 potential IAS on a 5-point scale for the likelihood of entry and establishment, potential socio-economic impact, and impact on biodiversity. The individual scores were combined to rank the species according to their overall potential risk for the country. Confidence in individual and overall scores was recorded on a 3-point scale. This resulted in a priority list of 120 potential IAS (70 arthropods, 9 nematodes, 15 bacteria, 19 fungi/chromist, 1 viroid, and 6 viruses). Options for risk mitigation such as full pest risk analysis and detection surveys were suggested for prioritised species while species for which no immediate action was suggested, were added to the plant health risk register and a recommendation was made to regularly monitor the change in risk. By prioritising risks, horizon scanning guides resource allocation to interventions that are most likely to reduce risk and is very useful to National Plant Protection Organisations and other relevant stakeholders.

Feasibility of the Bag-Mediated Filtration System for Environmental Surveillance of Poliovirus in Kenya - Nicolette A. Zhou; Christine S. Fagnant-Sperati; Evans Komen; Benlick Mwangi; Johnstone Mukubi; James Nyangao; Joanne Hassan; Agnes Chepkurui; Caroline Maina; Walda B. van Zyl; Peter N. Matsapola; Marianne Wolfaardt; et al. (Food and Environmental Virology, 2020)
The bag-mediated filtration system (BMFS) was developed to facilitate poliovirus (PV) environmental surveillance, a supplement to acute flaccid paralysis surveillance in PV eradication efforts. From April to September 2015, environmental samples were collected from four sites in Nairobi, Kenya, and processed using two collection/concentration methodologies: BMFS (> 3 L filtered) and grab sample (1 L collected; 0.5 L concentrated) with two-phase separation. BMFS and two-phase samples were analyzed for PV by the standard World Health Organization poliovirus isolation algorithm followed by intratypic differentiation. BMFS samples were also analyzed by a cell culture independent real-time reverse transcription polymerase chain reaction (rRT-PCR) and an alternative cell culture method (integrated cell culture-rRT-PCR with PLC/PRF/5, L20B, and BGM cell lines). Sabin polioviruses were detected in a majority of samples using BMFS (37/42) and two-phase separation (32/42). There was statistically more frequent detection of Sabin-like PV type 3 in samples concentrated with BMFS (22/42) than by two-phase separation (14/42, p = 0.035), possibly due to greater effective volume assayed (870 mL vs. 150 mL). Despite this effective volume assayed, there was no statistical difference in Sabin-like PV type 1 and Sabin-like PV type 2 detection between these methods (9/42 vs. 8/42, p = 0.80 and 27/42 vs. 32/42, p = 0.18, respectively). This study demonstrated that BMFS can be used for PV environmental surveillance and established a feasible study design for future research.

α-Amylase Mediates Host Acceptance in the Braconid Parasitoid Cotesia flavipes - Gladys Bichang’a; Jean-Luc Da Lage; Claire Capdevielle-Dulac; Michel Zivy; Thierry Balliau; Kevin Sambai; Bruno Le Ru; Laure Kaiser; Gerald Juma; Esther Njoki Mwangi Maina; Paul-André Calatayud (Journal of Chemical Ecology, 2018)

Risk factors associated with occurrence of nematodes in free range pigs in Busia District, Kenya - John Maina Kagira; Paul Njuki Kanyari; Samuel Maina Githigia; Ndicho Maingi; James Chege Ng’ang’a; John Mwangi Gachohi (Tropical Animal Health and Production, 2012)

Introgressive hybridization of human and rodent schistosome parasites in western Kenya - MICHELLE L. STEINAUER; BEN HANELT; IBRAHIM N. MWANGI; GEOFFREY M. MAINA; LELO E. AGOLA; JOSEPH M. KINUTHIA; MARTIN W. MUTUKU; BEN N. MUNGAI; WADE D. WILSON; GERALD M. MKOJI; ERIC S. LOKER (Molecular Ecology, 2008)
Hybridization and introgression can have important consequences for the evolution, ecology and epidemiology of pathogenic organisms. We examined the dynamics of hybridization between a trematode parasite of humans, Schistosoma mansoni , and its sister species, S. rodhaini , a rodent parasite, in a natural hybrid zone in western Kenya. Using microsatellite markers, rDNA and mtDNA, we showed that hybrids between the two species occur in nature, are fertile and produce viable offspring through backcrosses with S. mansoni . Averaged across collection sites, individuals of hybrid ancestry comprised 7.2% of all schistosomes collected, which is a large proportion given that one of the parental species, S. rodhaini, comprised only 9.1% of the specimens. No F1 individuals were collected and all hybrids represented backcrosses with S. mansoni that were of the first or successive generations. The direction of introgression appears highly asymmetric, causing unidirectional gene flow from the rodent parasite, S. rodhaini, to the human parasite, S. mansoni. Hybrid occurrence was seasonal and most hybrids were collected during the month of September over a 2‐year period, a time when S. rodhaini was also abundant. We also examined the sex ratios and phenotypic differences between the hybrids and parental species, including the number of infective stages produced in the snail host and the time of day the infective stages emerge. No statistical differences were found in any of these characteristics, and most of the hybrids showed an emergence pattern similar to that of S. mansoni. One individual, however, showed a bimodal emergence pattern that was characteristic of both parental species. In conclusion, these species maintain their identity despite hybridization, although introgression may cause important alterations of the biology and epidemiology of schistosomiasis in this region.